The Influence Of Leadership And Communication On Employee Work Discipline At The Department Of Cooperatives, Small And Medium Enterprises, Industry And Trade In Medan City - Resti Alvi Syahri; Muhammad Yalzamul Insan; Samrin Samrin (Universitas Dehasen Bengkulu, 2026)
The research analysis aims to analyze the Influence of Leadership and Communication on Employee Work Discipline at the Cooperatives, Small and Medium Enterprises, Industry and Trade Office of Medan City. The data analysis technique used is the associative research method with the help of the SPSS version 23 program. This study uses multiple linear regression analysis. The sample in this study was 69 respondents. Primary data collection used a questionnaire. The results showed that the t-value of 4.041> t-table of 1.99 with a significant value of 0.000 <0.05, so the hypothesis H1 is accepted and H0 is rejected, meaning that leadership has a positive and significant effect partially on employee work discipline. The test results show a calculated t value of 2.711> t table of 1.99 with a significant value of 0.009 <0.05, so the hypothesis H2 is accepted and H0 is rejected, meaning that communication has a positive and significant partial effect on employee work discipline. The results of the simultaneous test with a calculated F value of 18,817 which is greater than 3,14 and a significant value of 0.000 which is smaller than 0.05 so it can be concluded that leadership and communication have a significant effect simultaneously on employee work discipline.